2020
DOI: 10.1136/bmjopen-2019-033741
|View full text |Cite
|
Sign up to set email alerts
|

Estimating expected life-years and risk factor associations with mortality in Finland: cohort study

Abstract: ObjectiveTo develop a tool to inform individuals and general practitioners about benefits of lifestyle changes by providing estimates of the expected age of death (EAD) for different risk factor values, and for those who plan and decide on preventive activities and health services at population level, to calculate potential need for these.DesignProspective cohort study to estimate EAD using a model with 27 established risk factors, categorised into four groups: (1) sociodemographic background and medical histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Similar research results indicating the benefits of physical activity in older adults were shown in studies by Aguilar-Latorre et al [ 13 ], Härkänen et al [ 14 ], and Kim et al [ 15 ].…”
Section: Introductionsupporting
confidence: 87%
“…Similar research results indicating the benefits of physical activity in older adults were shown in studies by Aguilar-Latorre et al [ 13 ], Härkänen et al [ 14 ], and Kim et al [ 15 ].…”
Section: Introductionsupporting
confidence: 87%
“…Long-term illnesses and multimorbidity have become more common, thus reducing quality of life and increasing the demand for health care services [1,2]. Lifestyle choices have a significant impact on the expected onset of diseases, age of death, risk factors concerning long-term illnesses, and multimorbidity [1,[3][4][5]. Preventable lifestyle-related risk factors affecting chronic morbidity and mortality have been recognized, most notably smoking, the harmful use of alcohol, physical inactivity, and an unhealthy diet [5,6].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Among the well-established risk factors determining longevity recognized to date are smoking habits [ 12 , 13 ], diabetes mellitus [ 14 ], obesity [ 14 ], cardiovascular health [ 15 ], and sedentary lifestyle [ 15 ]. While it is generally recognized that married people live longer [ 16 , 17 ] and the very presence of social relationships in one’s life has a positive effect on one’s health and longevity [ 18 , 19 , 20 ], few studies so far have examined the impact of quality of midlife family relationships on survival among men. Fewer studies still focused on the conjunction of physiological, behavioral, and psychological factors and their effect on longevity.…”
Section: Introductionmentioning
confidence: 99%